2018
DOI: 10.32794/mr11250007
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline induced disruption of endogenous melatoninergic system, antioxidant and inflammatory responses in the gastrointestinal tissues of male Wistar rat: an in vitro study

Abstract: The current study aimed to demonstrate the potentially adverse effects of adrenaline, an endogenous stressor, on the melatonergic system, oxidative status, antioxidative responses and inflammatory markers in different parts of gastrointestinal tract of Wistar rat. These included stomach, duodenum and colon and they were incubated with different concentrations (2.5, 5.0 and 10.0 µg/mL) of adrenaline for 1h, respectively. The levels of melatonin, gene expressions of arylalkylamine N-acetyltransferase (AANAT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 38 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…Several animal studies have confirmed these similar observations (8,9,13,43,44). The PCO is a common marker of protein oxidative damage (8,9,45,46). The increased tissue levels of PCO indicate structural and functional damage of proteins linked to the auto-oxidation of adrenaline.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Several animal studies have confirmed these similar observations (8,9,13,43,44). The PCO is a common marker of protein oxidative damage (8,9,45,46). The increased tissue levels of PCO indicate structural and functional damage of proteins linked to the auto-oxidation of adrenaline.…”
Section: Discussionmentioning
confidence: 78%
“…Increased levels of LPO in GI tissues might be a consequence of oxidative injury caused by high dose of adrenaline (42). Several animal studies have confirmed these similar observations (8,9,13,43,44). The PCO is a common marker of protein oxidative damage (8,9,45,46).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Melatonin plays a remarkable role in the synchronisation of circadian rhythm, regulation of seasonal reproduction and enhancement of immune function in vertebrates (3). It is also a potent and broad spectrum antioxidant (3)(4)(5). Melatonin executes its antioxidant activities by up-regulation of the antioxidant enzymes, down-regulation of the pro-oxidant enzymes and directly detoxification of the free radicals (6,7).…”
Section: Introductionmentioning
confidence: 99%